Konstitusi dan Kewarganegaraan : Implikasi Yuridis dari Perubahan Pasal – Pasal UUD 1945 Terkait Kewarganegaraan - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; Fadhil Abdulloh; Elsa Fikry Nurcahya; Nihayatun Nisa (Majelis: Jurnal Hukum Indonesia, 2024)
This study looks at the legal ramifications of changing the Republic of Indonesia's 1945 Constitution's articles pertaining to citizenship (UUD 1945). The complexity of citizenship issues has increased with globalization, especially when it comes to dual citizenship and the rights of Indonesians residing outside. This study is classified as doctrinal research since it examines legal sources to determine legal principles. The study finds that amendments to the UUD 1945 are necessary to better align Indonesia's citizenship policies with global developments. However, these changes must be carefully considered to protect human rights and maintain national loyalty and identity. Reforming Indonesia's citizenship laws should be done thoughtfully, with input from various stakeholders, to ensure the resulting policies are inclusive and adaptable to the current global context. This research aims to contribute significantly to the development of Indonesia's citizenship policies and to offer a foundation for policymakers in crafting regulations that are more responsive to global challenges.